(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article is a comparative study of philosophical views on the study of historical consciousness and memory in the formation of national-spirituality. Socio-spiritual factors in the formation of historical consciousness and memory in the context of globalization are also revealed.